Food insecurity status and associated factors among rural households in the north of Iran. Issue 3 (October 2021) - Shakiba, Maryam; Salari, Arsalan; Mahdavi-Roshan, Marjan
Background: Iran has been experiencing an accelerated change in the nutrition and health of its people, which has led to considerable variations in the country's nutritional status. Little is known about the food insecurity status in the north of Iran. Aim: The present study aimed to investigate the food insecurity status and factors associated with it in a rural area in the north of Iran. Methods: This cross-sectional study was conducted among 573 rural households in Guilan Province in the north of Iran. The food insecurity status of the households was measured using the Household Food Insecurity Access Scale. Data on the demographic characteristics of the households and their depression status were collected by interviewing the heads of the households. The socioeconomic status index of the households was constructed using factor analysis, and a multivariate ordinal logistic regression model was used to estimate the adjusted odds ratio of the independent predictors of food insecurity. Results: The results indicated that approximately half of the households (50.8%) had experienced mild (43.2%), moderate (6.5%) or severe (1.1%) food insecurity. The multivariate model showed that sex, age, depression status of the head of the household and having a patient with a chronic condition in the household were independently associated with food security status. Conclusions: This study showed that food insecurity was highly prevalent among rural households in the north of Iran. The study concludes that interventions with the aim of reducing the prevalence of food insecurity, depression and chronic diseases in the area can be effective in improving the nutritional status of the households.